PERANAN SERTA PENGEMBANGAN LINGKUNGAN BAHASA ARAB SEBAGAI STRATEGI UNTUK MENGATASI KELEMAHAN BERBICARA BAHASA ARAB - Muhammad kumaini; Mustar Mustar (Al-TARQIYAH: Jurnal Pendidikan Bahasa Arab, 2024)
The role of Arabic language villages for non-Arabs is something that cannot be avoided, due to the urgency of the Arabic language for current Arabic language students. An Arabic language village is an environment formed with special rules that are obeyed by anyone residing within it. This Arabic language village provides strong encouragement and motivation for anyone who wants to facilitate communication and other branches of Arabic language studies. Arabic language villages also aim to provide a sense of self-confidence as if one were in the Middle East or in an Arab country. There are many reasons why non-Arabs find it difficult to actively communicate using Arabic. Various motivations drive people to learn Arabic, including religious, economic, and social status motivations. Many Arabic language institutions and institutes already exist, but not many have been able to preserve Arabic language villages as learning media that serve as the main reference source and center for developing active and competitive Arabic speaking skills. Arabic language villages also function as a platform to recognize and describe the Arabic language village environment, including strategies, influential factors within the Arabic language environment, and the role of Arabic language villages in developing Arabic communication proficiency.